MODEL PEMBERDAYAAN PEREMPUAN MISKIN MELALUI PELATIHAN KEWIRAUSAHAAN BERBASIS POTENSI LOKAL DI KECAMATAN WEDI KABUPATEN KLATEN - Agung Utama; Titin Hera Handayani (LPPM UNY, 2014)
his research is aimed to: depict the pro ile of the poor women in Kecamatan Wedi, Kabupaten Klaten, doing measurement towards the potential of entrepreneurship spirit of the poor women in Kecamatan Wedi, Kabupaten Klaten, and understanding the effectiveness of project based model (PBL) as the model of entrepreneurship training for the poor women in Kecamatan Wedi, Kabupaten Klaten based on their local resources. Data were collected from the secondary data and primary data. Data were analysed using the interactive model analysis. The result of this research showed that the poor women at Kecamatan Wedi: 1) live in dirty houses, have limited acces of primary education and the lower salary, 2) have high spirit for doing entrepreneurship. It indicates that they have a high potential for success if they get appropriate treatment of entrepreneurship, 3) have a high performance as an entrepreneur since the get entrepreneurship training using the PBL model. It is indicated that the model has a high effectiveness to use as a model of training